Distribution and diversity of gastropod from Bintulu rocky shore - Yusri Fakhri Yusop. (Universiti Putra Malaysia, 2014)
A study on invertebrate gastropod was carried out in three different sites which are Tanjung Batu, Pantai Telekom and Kuala Nyalau rocky shore area in Bintulu coastal are. This study was aimed to study the distribution pattern and diversity of gastropod from Bintulu rocky shore. Sampling was conducted during low tide from October 2013 until February 2014 following the NaGISA (Natural Geography in Shore Areas) standard protocal. A total of 29 species from 15 families were recorded. The highest species was found in Kuala Nyalau with 21 species and the lowest was found in Pantai Telekom with eight species. With high number of species, Kuala Nyalau was recorded the highest richness and diversity index with 2.6197 and 1.9669 while the lowest was Pantai Telekom with 1.1267 and 0.8983. Evenness index shown the highest was Kuala Nyalau with 0.6460 and the lowest was Tanjung Batu with 0.4224. The highest abundance was Nodilittorina pyramidalis with 1755 while the least abundance were Leamodonta cubensis, Hemifusus tuba, Morula granulata, Natica sp. (Unidentified 1), Philine angasi, and Monodonta labio with one individual for each species.